Oral administration of alkaloid fraction from Ruta graveolens inhibits oxidative stress and inflammation in hypercholesterolemic rabbits. (13th September 2013) - Ratheesh, M.; Helen, A.
Abstract: Context : The anti-atherogenic effect of alkaloid fraction from Ruta graveolens Linn (Rutaceae) extract is suspected to be related to its activities of antioxidation and anti-inflammation. Objective : This study investigated the efficacy of alkaloid fraction isolated from Ruta graveolens (AFR) in reducing oxidative damage and inflammation in hypercholesteremic rabbits. Materials and methods : The New Zealand white rabbits were randomly divided into three groups: Group I rabbits were fed with normal chow diet for 90 d. Group II rabbits were fed with 1% cholesterol-enriched diet. Group III rabbits were fed with 1% cholesterol-enriched diet together with AFR (10 mg/kg/daily for 90 d). Results and discussion : The results showed that on treatment with AFR significantly lowered the level of total cholesterol and LDL-C and showed an increment in the level of HDL-C. LD50 of the AFR in rats is greater than 525 mg/kg. Activities of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase and GSH level were decreased in cholesterol-fed rabbit and supplementation of AFR significantly enhanced the activities of these antioxidant enzymes and GSH level. Increased activities of enzymes such as cyclooxygenase-2, 15-lipoxygenase and myeloperoxidase were significantly suppressed by AFR administration. The acute phase proteins, total WBC count and TBARS concentrations were significantly increased by hypercholesteromic diet, which were significantly decreased by AFR treatment. Histopathological studies of aorta in cholesterol-fed rabbit showed plaque formation and significant changes in aortic wall. Administration of AFR showed no changes in aortic wall. Conclusion : AFR reduces oxidative stress and inflammation and reduces the aortic pathology in hypercholesteromic rabbits.